Effects of Saccharomyces cerevisiae fermentation derived postbiotic supplementation in sow and piglet diet on the fecal Escherichia coli counts and antimicrobial resistance in sucking piglets under intensive production system - Chao, N. V.; Hung, P. H. S.; Thao, L. D.; Dung, H. T.; Hoa, N. T.; Hien, B. T.; Mondal, A.; Nsereko, V. L.; Phung, L. D. (Diponegoro University, 2025)
This study evaluated the effects of SS. cerevisiae fermentation derived postbiotic (XPC) on fecal E. coli counts and antimicrobial resistant (AMR) in piglets with a high-biosecurity system. Thirty sows were divided into three groups: a standard basal diet (CON), CON with 1.0 kg/MT of Beta Beta-glucan 50% (BG), CON with 2.0 kg/MT of XPC (XPC). These diets were administared to sows from conception until weaning of the piglets, and to their piglets from 7 days old until weaning. Fecal samples were collected from piglets at 7, 14, and 21 days old for enumeration of E. coli . The disk diffusion and PCR methods were used to test for AMR and detect antimicrobial resistance genes (ARGs) in the isolates. Results showed XPC supplement significantly reduced E. coli counts (log10 CFU/g) than the CONgroup (p = 0.001). XPC decreased the frequency of E. coli isolateisolates resistance to ampicilin, erythromycin, and oxytetracyclin oxytetracycline (p < 0.05), while BG reduced resistance to cefotaxime, and gentami-cin (p < 0.05). Overall, dietary XPC supplementation in sows and piglets reduced E. coli counts in suckling piglets. Additionally, the diatary XPC and BG BG-50 supplementation was affected on the levelof AMR in E. coli .